Skeletal outcome in long-term survivors of childhood high-risk neuroblastoma treated with high-dose therapy and autologous stem cell rescue - Utriainen, P; Vatanen, A; Toiviainen-Salo, S; Saarinen-Pihkala, U; Mäkitie, O; Jahnukainen, K (Bone marrow transplantation (Basingstoke), 2017)
High-dose therapy and hematopoietic stem cell transplantation (HSCT) have been shown to improve survival rates in high-risk neuroblastoma (HR-NBL), but may cause adverse effects on the growing skeleton. We studied skeletal health in a national cohort of long-term survivors of HR-NBL ( n =21; age 16–30 years, median 22 years) and in 20 healthy age- and sex-matched controls. In addition to clinical evaluation and measurement of bone mineral density (BMD) by dual-energy X-ray absorptiometry, we performed spinal magnetic resonance imaging. Skeletal complications were categorized according to Common Terminology Criteria for Adverse Events (CTCAE). Altogether, 18/21 survivors presented with at least one skeletal adverse event according to CTCAE, the most common skeletal complications being short stature ( n =14) and osteopenia ( n =13). Altogether, 38% of the subjects had a severe complication (CTCAE score ⩾3) including bilateral slipped capital femoral epiphyseolysis in 3/21. Fracture rate was not increased. In spinal MRI, no vertebral fractures were found and degenerative intervertebral disc changes were equally prevalent in survivors and controls. BMD was lower in survivors than controls, but differences became non-significant when adjusted for bone size. In conclusion, skeletal late complications are common and can significantly impair the quality of life in young adult survivors of HR-NBL treated with high-dose protocols and HSCT.